Benchmarking Hospitality Management Curricula: A Comparison of Top U.S. Programs—A Repeat Study. Issue 3 (3rd July 2019) - Szende, Peter; Catalfamo, Nicholas; Upneja, Arun
ABSTRACT: More than 18 years ago, scholars from Pennsylvania State University captured the structure of undergraduate hospitality course offerings in 16 leading U.S. schools (Bartlett, Upneja, & Lubetkin, 1998). Considerable time has elapsed since the publication of that original article. This study serves as a useful update to the original study and adds incremental value by comparing current course offerings to those discussed in the previous research while also attempting to identify changes that have occurred in response to and as a result of new trends. Our selection process resulted in a final sample of 21 schools to pinpoint relevant trends under the applied criteria. This article aims to offer guidance and insight to curriculum developers about how to improve hospitality curricula. The information offers guidance to curriculum developers and can serve as a benchmark for future studies.